AKTIVITAS FISIK, ASUPAN ENERGI, DAN PRODUKTIVITAS KERJA PRIA DEWASA: STUDI KASUS DI PERKEBUNAN TEH MALABAR PTPN VIII BANDUNG, JAWA BARAT - Noni Eka Jaya Wardani; Katrin Roosita (Jurnal Gizi dan Pangan, 2008)
The cross sectional design was used in this study to elaborate physical activity, energy consumption, and work productivity of men workers. The total number of sample is 72 men.  The inclusion criteria of  the sample is the head of household’s women tea pickers at Tea Plantation PTPN VIII Bandung, West Java who have children 0-72 month age and willing to be interviewed. The place of the research was chose purposively. Malabar Plantation was chosen from the other five plantations (clusters) cause of its easier access and the homogenous characteristics inter cluster. Data collected was analyzed statistically. In general, more than a half of samples had  active or moderately physical activity  level (PAL=1.89). The physical activity level of samples during work day (average PAL=1.93) was higher than holiday (average PAL=1.77) (p<0.05). The working hours during holiday were substituted by doing domestic chores and miscellaneous recreational activities. There are significant differences (p<0.05) of energy requirement based on three calculation (Schofield equation, Oxford equation, and energy RDI on WNPG (2004)). Average energy consumption of men workers were 87.2 - 121.2%.  Majority of samples (76.4%) had wages per month below the regional minimum wages. The working hours of more than a half of samples were below seven hours per day and had wages per hour below standard regional minimum wage. Based on correlation analysis, there are significant correlation between 1) education level with physical activity level; 2) age, income per capita, and family size with wage per month; 3) age and physical activity level with working hours; and 4) age and  income per capita with wages per hour.